Partnering with women collectives for delivering essential women's nutrition interventions in tribal areas of eastern India: a scoping study - Vani Sethi; Arti Bhanot; Surbhi Bhalla; Sourav Bhattacharjee; Abner Daniel; Deepika Mehrish Sharma; Rajkumar Gope; Saba Mebrahtu (BMC, 2017)
Abstract Background We examined the feasibility of engaging women collectives in delivering a package of women's nutrition messages/services as a funded stakeholder in three tribal-dominated districts of Odisha, Jharkhand and Chhattisgarh States, in eastern India. These districts have high prevalence of child stunting and poor government service outreach. Methods Conducted between July 2014 and March 2015, an exploratory mix-methods design was adopted (review of coverage data and government reports, field interviews and focus group discussion with multiple stakeholders and intended communities) to assess coverage of women's nutrition services. A capacity assessment tool was developed to map all types of community collectives and assess their awareness, institutional and programme capacity as a funded stakeholder for delivering women's nutrition services/behaviour promotion. Results Limited targeting of pre-pregnancy period, delays in first trimester registration of pregnant women, and low micronutrient supplementation supply and awareness issues emerged as key bottlenecks in improving women's nutrition in these districts. Amongst the 18 different types of community collectives mapped, Self Help Groups (SHGs) and their federations (tier 2 and tier 3), with total membership of over 650,000, emerged as the most promising community collective due to their vast network, governance structure, bank linkage, and regular interface. Nearly 400,000 (or 20% of women) in these districts can be reached through the mapped 31,919 SHGs. SHGs with organisational readiness for receiving and managing grants for income generation and community development activities varied from 41 to 94% across study districts. Stakeholders perceived that SHGs federations managing grants from government and be engaged for nutrition promotion and service delivery and SHG weekly meetings can serve as community interface for discussing/resolving local issues impeding access to services. Conclusions Women SHGs (with tier 2 and tier 3) can become direct grantees for strengthening coverage of women's nutrition interventions in these tribal districts/pockets, provided they are capacitated, supervised and given safe guards against exploitation and violence.